Mechanochemical preparation of piezoelectric nanomaterials: BN, MoS2 and WS2 2D materials and their glycine-cocrystals. Issue 2 (18th October 2019) - González, Viviana Jehová; Rodríguez, Antonio M.; Payo, Ismael; Vázquez, Ester
Abstract : Different 2D-layered materials of transition metal dichalcogenides (TMDCs) such as boron nitride (BN) or molybdenum disulphide (MoS2 ) have been theorised to have piezoelectric behaviour. Abstract : Different 2D-layered materials of transition metal dichalcogenides (TMDCs) such as boron nitride (BN) or molybdenum disulphide (MoS2 ) have been theorised to have piezoelectric behaviour. Still, the procedures to obtain these nanomaterials, with the right quality and quantity to observe the piezoelectric performance, are enormously expensive, halting their possible applications. Here, we show the mechanochemical exfoliation of 2D nanomaterials (FLG, BN, MoS2 and WS2 ) with glycine. We have also successfully synthesised the cocrystals for these nanomaterials, which makes it possible to enhance their piezoelectric responses.